Aktivitas Antioksidan, Kadar Serat dan Karakteristik Fisik Beras Hitam Pecah Kulit Pratanak dengan Variasi Lama Waktu Perendaman - Salsabila Amalia Putri Bumi; siti aminah; muhammad yusuf (Jurnal Pangan dan Gizi, 2020)
Black rice has a better bioactive component than white rice. The quality of black rice can be increased, among others, through the process of  the broken skin grinding. Black broken rice has a better nutritional and bioactive component than polished rice. But black broken rice skin is easily damaged. One that can be done is processing into parboiled rice. The purpose of this study in general was to determine antioxidant activity, fiber content and the characteristics of black rice broken pre pared skin. The experimental design used was a monofactor Completely Randomized Design (RAL) with variations in the length of immersion time (0, 30, 60, 90, 120, 150 and 180 minutes). Analysis was carried out on antioxidants, fiber content and physical characteristics (cage density, air absorbency, development ratio, bulk angle and broken grain) black broken rice skin with parboiled. The results of the study stated that the treatment of soaking black rice caused a decrease in antioxidant activity and crude fiber. The highest decreased in the 180 minutes immersion treatment with a decrease in presentation was 35% and 10,2% respectively, the results of testing on physical characteristics showed immersion treatment had an effect on decreasing in the kamba density test, development ratio, bulk angle and broken grain. However, the water absorption test experienced an increase. The best treatment is in a variation of 30 minutes soaking time.